Pas de Trois: An Overview of Penta-, Tetra-, and Octo-Tricopeptide Repeat Proteins From Chlamydomonas reinhardtii and Their Role in Chloroplast Gene Expression - Macedo-Osorio, Karla S.; Martínez-Antonio, Agustino; Badillo-Corona, Jesús A. (Frontiers in Plant Science, 2021)
Penta-, Tetra- and Octo-tricopeptide repeat (PPR, TPR, and OPR) proteins are nucleus-encoded proteins composed of tandem repeats of 35, 34, and 38-40 amino acids, respectively. They form helix-turn-helix structures that interact with mRNA or other proteins and participate in RNA stabilization, processing, maturation, and act as translation enhancers of chloroplast and mitochondrial mRNAs. These helical repeat proteins are unevenly present in plants and algae. While PPR proteins are more abundant in plants than in algae, OPR proteins are more abundant in algae. In Arabidopsis, maize, and rice there have been 450, 661, and 477 PPR proteins identified, respectively, which contrasts with only 14 PPR proteins identified in Chlamydomonas reinhardtii. Likewise, more than 120 OPR proteins members have been predicted from the nuclear genome of C. reinhardtii and only one has been identified in Arabidopsis thaliana. Due to their abundance in land plants, PPR proteins have been largely characterized making it possible to elucidate their RNA-binding code. This has even allowed researchers to generate engineered PPR proteins with defined affinity to a particular target, which has served as the basis to develop tools for gene expression in biotechnological applications. However, fine elucidation of the helical repeat proteins code in Chlamydomonas is a pending task. In this review, we summarize the current knowledge on the role PPR, TPR, and OPR proteins play in chloroplast gene expression in the green algae C. reinhardtii, pointing to relevant similarities and differences with their counterparts in plants. We also recapitulate on how these proteins have been engineered and shown to serve as mRNA regulatory factors for biotechnological applications in plants and how this could be used as a starting point for applications in algae.